MENGATASI KRISIS KEDELAI NASIONAL - Ningsih, Gumoyo Mumpuni (Jurnal Bestari, 2008)
The phenomena of food scarcity, like soy scarcity in Indonesia should not probably happen if the consumers consume the soybean of national product. Starting from the habit of consuming imported soybean and it leads to the dependency to the imported soybean, the product of the domestic soy started to decrease. In turn, when we face the crisis of soybean, the consumers, mostly the producer of rempe and tabu have to suffer for this burden because of the rocketing price. It seems ironical that Indonesia that has rich and extensive farmland facing the problem of soybea n scarcity. To promote the growth of soybean in Indonesia. the producer of tempt, and talus have to care of the nation's soybean product. Farmers have to use their effort to produce soybean needed by the producers. Finally, government must pay their attention and effort to enhance the soybean sufficiency, both in short and long period.